IDENTIFYING FACTORS INFLUENCING SCHOOL LEADERSHIP PRACTICES: CASE STUDY OF LATVIA - Saleniece, Ilze; Namsone, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Based on the analysis of research literature and empirical data, the study aims to identify significant factors affecting school leadership practices in Latvia. In addition to studies of scientific literature, the authors used qualitative research methods – in-depth interviews with 7 school leadership teams of the same municipality and expert focus group discussion to describe the influencing factors that are relevenat in the context of Latvia. As a result of the study, the authors identified that school leaders’ work experience, beliefs and mental models, social skills and impact of the external parties have an influence on their practices.